2022
DOI: 10.1136/bmjgh-2022-009762
|View full text |Cite
|
Sign up to set email alerts
|

A study of the quality of cardiovascular and diabetes medicines in Malang District, Indonesia, using exposure-based sampling

Abstract: BackgroundThe WHO has warned that substandard and falsified medicines threaten health, especially in low and middle-income countries (LMICs). However, the magnitude of that threat for many medicines in different regions is not well described, and high-quality studies remain rare. Recent reviews of studies of cardiovascular and diabetes medicine quality recorded that 15.4% of cardiovascular and 6.8% of diabetes samples failed at least one quality test. Review authors warn that study quality was mixed. Because t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…21 The study methods are reported in detail elsewhere, according to MEDQUARG guidelines. 22 The MEDQUARG checklist is available in the study archive. 23 Briefly, we designed an exposure-based sample frame.…”
Section: Methodsmentioning
confidence: 99%
“…21 The study methods are reported in detail elsewhere, according to MEDQUARG guidelines. 22 The MEDQUARG checklist is available in the study archive. 23 Briefly, we designed an exposure-based sample frame.…”
Section: Methodsmentioning
confidence: 99%
“…No amlodipine sample failed assay or dissolution testing, a result consistent with findings in an earlier study of cardiovascular and diabetic medicines conducted in just one district of Indonesia. 18 At the other extreme, one in five of the 75 samples of amoxicillin dry syrup contained below the permitted amount of active ingredient. Failure on both assay and dissolution were also high for cefixime, at 7.7% and 14.4% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…At least two studies have attempted to account for these variations in market share, the first, in DRC Congo, by weighting prevalence by distributor sales volume, 17 and the second, in Indonesia, in its sampling design 18 . In Congo, researchers found that poor quality products had smaller distribution, so the overall prevalence of substandard medicines was lower than raw prevalence estimates would suggest.…”
Section: Introductionmentioning
confidence: 99%
“…This study was nested in a larger study of the quality of cardiovascular medicines in Malang District, involving the collection of medicine distribution and price data, and in-depth interviews with individuals with either direct experience, or knowledge of, the landscape relating to CVD medicines in Malang, including funding, pricing, procurement, distribution, prescription, dispensing and record-keeping [17]. Potential participants were approached by e-mail outlining details of the study and requesting their participation; those who agreed to participate provided verbal or written consent, including for the recording of interviews.…”
Section: Participant Recruitment and Consentmentioning
confidence: 99%